Corruption, nepotism and the dynamics of leadership : reading Mark 10:35-45 and Matthew 20:20-28 with Angolan eyes - Panda, Teresa Chateia David (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2024.